Development of S Haplotype-Specific Markers to Identify Genotypes of Self-Incompatibility in Radish (Raphanus sativus L.) - Seong-Ho Heo; Su-Yeon Kim; Suk-Yeon Mo; Han-Yong Park (Plants, 2024)
Radish (Raphanus sativus L.), a root vegetable belonging to the Brassicaceae family, is considered one of the representative crops displaying sporophytic self-incompatibility (SSI). The utilization of a self-incompatibility system in F1 breeding can improve the efficiency of cross-combinations, leading to a reduction in breeding time and aiding in the development of novel F1 varieties. The successful implementation of this system necessitates the rapid and accurate identification of S haplotypes in parental lines. In this study, we identified a total of nine S haplotypes among 22 elite radish lines through Sanger sequencing. Subsequently, we obtained sequences for showing a 95% similarity to nine S haplotypes, along with sequences identified by other researchers using BLAST. Following this, multiple sequence alignment (MSA) was conducted to identify SRK and SLG sequence similarities, as well as polymorphisms within the class I and II groups. Subsequently, S haplotype-specific marker sets were developed, targeting polymorphic regions of SRK and SLG alleles. These markers successfully amplified each of the nine S haplotypes. These markers will play a crucial role in the rapid and precise identification of parental S haplotypes in the radish F1 breeding process, proving instrumental in the radish F1 purity test.